2017
DOI: 10.1159/000485030
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of the Promotor Region of Vascular Endothelial Growth Factor-A and Nerve Growth Factor in Opioid-Maintained Patients

Abstract: Aims: The nerve growth factor (NGF) and the vascular endothelial growth factor-A (VEGF-A) may be of importance for psychiatric diseases including substance use disorders. The aim of the study was to identify differences in the regulation of both neuropeptides via the DNA-methylation status of the promotor regions of NGF and VEGF-A in different forms of maintenance therapy for opioid dependence and the related stress regulation via the hypothalamic-pituitary-adrenal axis. Methods: We compared methylation levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…DNA methylation occurs mostly on cytosine residues positioned in CpG islands (high density of CG dinucleotides) within a promoter region, transcription start site (TSS), first or second exons of a gene, in an enhancer region, or upstream from genes with CpG island shores (2 kb) or CpG shelves (2-4 kb) [2]. Previous studies have shown that epigenetics plays an important role in the regulation of promoter regions of VEGFA [22,23] and VEGFR genes [24,25], but no previous research studies have performed an EWAS of VEGF-A concentration to determine the methylation sites responsible for the regulation of VEGFA. As VEGF-A plays a distinct role in the development of several chronic diseases, the discovery of its epigenetic regulation mechanisms may contribute to a better understanding of these disorders and contribute in the research of new therapeutic possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation occurs mostly on cytosine residues positioned in CpG islands (high density of CG dinucleotides) within a promoter region, transcription start site (TSS), first or second exons of a gene, in an enhancer region, or upstream from genes with CpG island shores (2 kb) or CpG shelves (2-4 kb) [2]. Previous studies have shown that epigenetics plays an important role in the regulation of promoter regions of VEGFA [22,23] and VEGFR genes [24,25], but no previous research studies have performed an EWAS of VEGF-A concentration to determine the methylation sites responsible for the regulation of VEGFA. As VEGF-A plays a distinct role in the development of several chronic diseases, the discovery of its epigenetic regulation mechanisms may contribute to a better understanding of these disorders and contribute in the research of new therapeutic possibilities.…”
Section: Introductionmentioning
confidence: 99%